Disease Severity, Fever, Age, and Sex Correlate With SARS-CoV-2 Neutralizing Antibody Responses - Schlickeiser, Stephan; Schwarz, Tatjana; Steiner, Sophie; Wittke, Kirsten; Al Besher, Nabeel; Meyer, Oliver; Kalus, Ulrich; Pruß, Axel; Kurth, Florian; Zoller, Thomas; Witzenrath, Martin; Sander, Leif Erik; et al. (Frontiers in Immunology, 2021)
SARS-CoV-2 convalescent plasma continues to be a plausible treatment option in COVID-19. While data on safety is increasingly available, evidence for efficacy is still sparse. Subgroup analyses hint to a dose-response relationship between convalescent plasma neutralizing antibody levels and mortality. In particular, patients with primary and secondary antibody deficiency might benefit from this approach. However testing of neutralizing antibodies is limited to specialized biosafety level 3 laboratories and is a time- and labor-intense procedure. In this single center study of 206 SARS-CoV-2 convalescent patients, clinical data, results of commercially available ELISA testing of SARS-CoV-2 spike-IgG and –IgA and levels of neutralizing antibodies, determined by plaque reduction neutralization testing (PRNT), were analyzed. At a medium time point of 58 days after symptom onset, only 12,6% of potential plasma donors showed high levels of neutralizing antibodies (PRNT50 > 1:320). Multivariate proportional odds logistic regression analysis revealed need for hospitalization due to COVID-19 (OR 6.87; p value 0.0004) and fever (OR 3.00; p value 0.0001) as leading factors affecting levels of SARS-CoV-2 neutralizing antibody titers in convalescent plasma donors. Using penalized estimation a predictive PO logistic regression model including the most important variables hospitalization, fever, age, sex and anosmia or dysgeusia, was developed. The predictive discrimination for PRNT50 > 1:320 was reasonably good with AUC: 0.86 (with 95% CI: 0.79-0.92). Combining clinical and ELISA-based pre-screening, assessment of neutralizing antibodies could be spared in 75% of potential donors with a maximal loss of 10% of true positives (PRNT50 > 1:320).